EVALUATION OF SERUM BUTRYLCHOLINESTERASE ACTIVITY AS BIOMARKER FOR PREDICTING RISK OF ISCHEMIC HEART DISEASE - GIRISH M.DESAI,; RAGHUNANDANA .R,; ANAND K.BOYAPATI,; ARCHANA C.NANDYAL, (International Journal of Pharma and Bio Sciences, 2014)
The incidence, prevalence, mortality and morbidity of ischemic heart disease is increasing allover the world. Early detection and prevention of ischemic heart disease is important. Hence, identification of biomarkers for cardiovascular disease and its risk factors is needed.Aims and objectives of this study was to evaluate the association of butrylcholinesterase activity with lipid risk ratios in ischemic heart disease. Materials & Methods: The cross sectional comprises 50 healthy subjects and equal number of myocardial infarction cases. Serum butrylcholinesterase activity, lipid profile was estimated and lipid ratios were calculated. Data was statistically analyzed.In our study , serum butrylcholinesterase activity was increased in myocardial infarction cases and correlated with lipid ratios in them . Serum butrylcholinesterase activity may be used in clinical practice as an tool for prediction of ischemic heart disease.